Upaya Pengolahan Limbah Kotoran Babi Menggunakan Komposter Rumah Tangga - Sari, Widya; Budiarsa Suyasa, I Wayan; Sila Dharma, I.G.B (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 12 No 2 (2018)DO - 10.24843/EJES.2018.v12.i02.p01, 2018)
ABSTRACT        The production of pig manure waste potentially pollutes the soil, water and air. One of the most effective processing a waste treatments is through composting. The composting process takes a long time if not assisted by the activator as decomposers of organic materials in order to accelerate the composting process. Activators such as local microorganism (MOL) contain macro nutrients, micro and active microorganism that potentially decomposed organic materials, growth stimulants and pest/disease control agents such as to help speed up the composting process. This study aims to determine the C/N ratio of optimal raw materials for composting of pig manure and vegetable waste, determining the effect of adding local microorganism (MOL) to the length of time of composting and determining the effectiveness of business from composting of pig manure and vegetable waste based on the calculation of B/C ratio.        This research uses quantitative approach with experiment method. The first stage is the preparation of the raw material which is divided into three groups : composition 1 with 75% (pig manure) and 25% (vegetable waste), composition 2 with 50% (pig manure) and 50% (vegetable waste) and then composition 3 with 25% (pig manure) and 75% (vegetable waste). Furthermore, the best raw material composition was treated with variations of MOL addition of A (100 ml), B (300 ml), C (500 ml) and D (without MOL).        The results showed that the composition of the best raw material mixture was a mixture composition of 25% (pig manure) and 75% (vegetable waste) with a C/N ratio of 38.95. The effect of MOL addition indicates that the greater MOL volume the faster to composting process. The quality compost with addition of MOL has C/N ratio levels is (16,30), N-total (1,65%), P tersedia (8043,02 ppm), K tersedia (8857,40 ppm), Fe (1,87%), Mn (0,09%) Zn (480 ppm) in which that value meets the SNI 19-7030-2004. Based on analysis of B/C ratio obtained result of 1.04 where the value is approaching criteria B/C ratio more than 1.00 which means compost business feasible to be developed.   Keywords : Pig manure, MOL, time of composting, composter, B/C ratio